Information Technology and Political Engagement: Mixed Evidence from Uganda - Guy Grossman; Macartan Humphreys; Gabriella Sacramone-Lutz (The Journal of Politics, 2020)
This study integrates three related field experiments to learn about how information communications technology (ICT) innovations can affect who communicates with politicians. We implemented a nationwide experiment in Uganda following a smaller-scale framed field experiment that suggested that ICTs can lead to significant “flattening”: marginalized populations used short message service (SMS) based communication at relatively higher rates compared to existing political communication channels. We find no evidence for these effects in the national experiment. Instead, participation rates are extremely low, and marginalized populations engage at especially low rates. We examine possible reasons for these differences between the more controlled and the scaled-up experiments. The evidence suggests that even when citizens have issues they want to raise, technological fixes to communication deficits can be easily undercut by structural weaknesses in political systems.
doi:10.7910/DVN/GBR02C
Keywords: 300